EXTRACT OF PROPOLIS IN THE TREATMENT OF CUCUMBER SEEDS AND CONTROL OF Aspergillus sp - de Souza, E.P.; Moscato, B.S.; Perino, F.H.B.; Nakada-Freitas, P.G.; Blumer, S.; Cardoso, A.I.I.; Bonini, C.S.B. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The alternative control has as characteristics the absence of contamination and social and environmental toxicity, and an alternative is the extract of propolis, which objectified with this work verify the effect of solutions of propolis extract in vitro control of the fungus Aspergillus sp, and the physiological quality of the cucumber seeds after treatment with the same solutions. Isolate from the fungus was inoculated in BDA medium with concentrations of 0; 8; 12; 18 and 25% of aqueous Propamax® extract, totaling five treatments. For the seed treatment, were used the same concentrations of propolis extract. The design was completely randomized with six replicates. It was verified that with the linear increase of the dose of the propolis extract, there was interference in the fungus development reaching maximum with 25%. Cucumber seeds treated with propolis solutions do not affect the physiological quality, resulting in a possible alternative seed treatment.